PENGARUH PENGGUNAAN HANDOUT TERHADAP HASIL BELAJAR FISIKA SISWA KELAS VIII SMP N 3 TUMIJAJAR - erni mariana (Pendidikan Kimia Unimus, 2020)
The selection of learning media must be considered several things, including the ease and use, handouts are learning media that are easy to make and use. This study aims to determine the effect of using handouts on the physics learning outcomes of grade VIII students of SMP Negeri 3 Tumijajar even semester. The research design used was Posttest-Only Control Design Design and the research instruments were observation sheets, questionnaire sheets and tests. The data analysis technique used is the calculation of the normality test, the homogeneity test, the two mean similarity test, and the two mean difference test. Research shows that the valuet of 3.49 was greater than ttable at 2.00 at significance level α = 5%, as well as the significance level α = 1%t is greater than ttable by 2.66. So the hypothesis which states that there is an effect of the use of handouts on the physics learning outcomes of grade VIII students of SMP N 3 Tumijajar even semester is accepted. The selection of learning media must be considered several things, including the ease and use, handouts are learning media that are easy to make and use. This study aims to determine the effect of using handouts on the physics learning outcomes of grade VIII students of SMP Negeri 3 Tumijajar even semester. The research design used was Posttest-Only Control Design Design and the research instruments were observation sheets, questionnaire sheets and tests. The data analysis technique used is the calculation of the normality test, the homogeneity test, the two mean similarity test, and the two mean difference test. Research shows that the valuet of 3.49 was greater than ttable at 2.00 at significance level α = 5%, as well as the significance level α = 1%t is greater than ttable by 2.66. So the hypothesis which states that there is an effect of the use of handouts on the physics learning outcomes of grade VIII students of SMP N 3 Tumijajar even semester is accepted.